Avaliação do efeito de gases poluentes na corrosão metálica: um experimento para o ensino da corrosão - Bidetti, Bárbara Bidoia [UNESP]; Balthazar, Priscila Aoki [UNESP]; Acciari, Heloisa Andréa [UNESP]; Codaro, Eduardo Norberto [UNESP] (Sociedade Brasileira de Química, 2011)
In this work one proposes a didactic experience to simulate atmospheric corrosion of copper and nickel, due to sulfur dioxide presence. This is an opportunity to understand some basic aspects of atmospheric corrosion, by using fundamental concepts in chemistry, reactions of extraction and characterization of pollutants, as well as their participation in corrosion process. This subject opens a space for discussion about necessity of pollutant gases emissions control for preservation of materials and the environment.
Evaluation of the effect of gaseous pollutants in metallic corrosion: an experiment for teaching of corrosion
Keywords: chemistry education; atmospheric corrosion; sulfur dioxide